PENERAPAN MEDIA AUDIO-VISUAL PADA PEMBELAJARAN IPA UNTUK MENINGKATKAN PEMAHAMAN SISWA SD - Sela, Maria Petrosia Wea; Dinatha, Ngurah Mahendra; Rewo, Josep Marsianus; Kua, Maria Yuliana (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Science learning at SDK Majamere is still conventional using the lecture method and without using learning media. This causes low student motivation to take part in learning, thus affecting students' understanding of science learning. This research aims to improve students' understanding after participating in learning using audio-visual media. The subjects of this research were 13 grade VI students at SDK Majamere. The type of research used is classroom action research. Research data was obtained through observation sheets. This research data consists of observed student activity data, namely asking questions, answering, recording important material, and providing suggestions. The results of the research showed that the results of questioning activities had increased, namely from 23.07% in cycle I to 84.61% in cycle II. Answering activity increased from 30.76% in cycle I to 76.92% in cycle II. The activity of recording important material has increased from 38.46% in cycle I to 92.30% in cycle II. The activity of providing advice increased from 15.38% in cycle I to 61.53% in cycle II. Based on the results of this classroom action research, it can be conclude that the application of audio visual media can improve the understanding of class VI students at SDK Majamere, Mauponggo District, Nagekeo Regency